Preparation and characterization of silicone rubber through the reaction between γ‐chloropropyl and amino groups with siloxane polyamidoamine dendrimers as cross‐linkers. (9th November 2017) - Dong, Fuying; Lu, Hang; Feng, Shengyu; Tang, Xinde
Abstract : A novel heat‐curable silicone rubber (MCSR/Si‐PAMAM) was prepared by using siloxane polyamidoamine (Si‐PAMAM) dendrimers as cross‐linkers and polysiloxane containing γ ‐chloropropyl groups as gums. The chemical cross‐linking occurs through the reaction between Si‐PAMAM dendrimers and polysiloxane containing γ ‐chloropropyl groups. The effect of various amounts of cross‐linkers on mechanical properties of MCSR/Si‐PAMAM was discussed in this paper. MCSR/Si‐PAMAM exhibits favorable mechanical properties with a tensile strength of 10.06 MPa and a tear strength of 47.9 kN/m when the molar ratio r of [N‐H]/[CH2 CH2 CH2 Cl] is 1:1. These excellent mechanical properties can be attributed to the formation of concentrative cross‐linking from Si‐PAMAM dendrimers in the cross‐linking networks, along with the introduction of Si–O–Si units in the internal structure of dendrimers. The introduction of Si–O–Si units reduces the steric hindrance of molecular structure, which facilitates the N–H bonds in the interior layers of dendrimers to react with γ ‐chloropropyl groups. In addition, thermogravimetric analysis results indicate that MCSR/Si‐PAMAM is thermally stable even at high temperatures in a nitrogen atmosphere. Differential scanning calorimetry analysis reveals that the glass transition peak of MCSR/Si‐PAMAM is not identified in the temperature range −150 to −30°C, only a melting endothermic peak at −40°C.